Krukenberg tumor arising from gastric cancer presenting as Pseudo-Meigs' syndrome: a case report and literature review - Qiu, Shikang; Jiang, Huihui; Ding, Hanxiao; Feng, Limin (Frontiers in Medicine, 2024)
Krukenberg tumor is a relatively uncommon metastatic ovarian cancer, typically presenting with abdominal pain and distension, primarily due to bilateral ovarian involvement. Pseudo-Meigs' syndrome, caused by a Krukenberg tumor originating from gastric cancer, is extremely rare. In this study, we report the case of a 39-year-old woman who presented with unusual manifestations of a Krukenberg tumor, where abdominal distension and dyspnea were the primary symptoms. After surgical treatment, a histopathological examination of the ovary revealed the presence of signet ring cell carcinoma. We concluded that this case coincided with Pseudo-Meigs' syndrome. Clinicians should note that Pseudo-Meigs' syndrome should be considered in patients with Krukenberg tumor, ascites, and pleural effusion, as resection of the tumor may provide long-term palliation.